Exploratory Factor Analysis of Online Teaching Effectiveness in Nursing Education - Catabona, Zuzette Basa (UM Purwokerto Press, 2025)
The rapid growth of online education has necessitated an in-depth investigation into the factors influencing teaching effectiveness in online learning environments. This study aims to identify and examine the key factors contributing to the online teaching effectiveness of nurse instructors through Exploratory Factor Analysis (EFA) and develop a tool to measure the Online Teaching Effectiveness (OTE) of nursing instructors. Preliminary item statements were developed based on a thorough review of relevant literature, resulting in a 49-item scale. A multidisciplinary panel member then validated the content, reducing it to a 48-item Content Validated item statement. Pilot testing with 596 third-level students from the College of Nursing at NEUST led to a final set of 41 items. The EFA in this study was carried out using a single random subsample of 410 Level IV Bachelor of Science in Nursing (BSN) student nurses from Higher Education Institutions across Luzon, Visayas, and Mindanao in the Philippines. All respondents were enrolled in the BSN program and participated in online education. This sample size adhered to the